Building Back Better : Achieving Resilience through Stronger, Faster, and More Inclusive Post-Disaster Reconstruction - Hallegatte, Stéphane; Rentschler, Jun; Walsh, Brian (World Bank, Washington, DC, 2018)
The 2017 Unbreakable report made the case that disaster losses disproportionately affect poor people. The Caribbean hurricane season of 2017 was a tragic illustration of this. Two category 5 hurricanes wreaked destruction on numerous small islands, causing severe damages on islands like Barbuda, Dominica, and Saint Martin. The human cost of these disasters was immense, and the impact of this devastation was felt most strongly by poorer communities in the path of the storms. And yet, amidst the destruction it is essential to look forward and to build back better. In this 2018 report the authors explore how countries can strengthen their resilience to natural shocks through a better reconstruction process. Reconstruction needs to be strong, so that assets and livelihoods become less vulnerable to future shocks; fast, so that people can get back to their normal life as early as possible; and inclusive, so that nobody is left behind in the recovery process. The benefits of building back better could be very large – up to US$173 billion per year globally – and would be greatest among the communities and countries that are hit by disasters most intensely and frequently and that have limited coverage of social protection and financial inclusion. Small island states – because of their size, exposure, and vulnerability – are among the countries where building back better has the greatest potential. A stronger, faster, and more inclusive recovery would lead to an average reduction in disaster-related well-being losses of 59 percent in the 17 small island states covered in the report.